Role of clean intermittent self-catheterization in prevention of recurent urethral stricture after optical internal urethrotomy - Bhatta, Pushupati Nath; Raya, Akash; Alam, Mohammad Shahid; Aryal, Rishikant; Dutta, Deepak Kumar (Journal of Physiological Society of Nepal, 2020)
Introduction: Urethral stricture is one of the common urological problem. There are different option to treat urethral stricture but, irrespective of the treatment the chances of recurrence is still high. Clean intermittent self-catheterization (CISC) was introduced by Lapides has greatly reduced the chances of recurrence. So, the objectives of this randomized clinical trial was to compare the chances of recurrence in optical internal urethrotomy (OIU) patients with or without CISC. Materials and methods: A randomized controlled study conducted in the department of surgery, urology division at National medical college, Birgunj from June 2019 to June 2020. Total 97 cases of age 20-80 years with stricture up to 1-2 cm were included. All cases were randomized in two groups. Group 1 (optical internal urethrotomy with clean intermittent self-catheterization) Group 2 (optical internal urethrotomy without clean intermittent self-catheterization). Results: Among total 97 cases 4 cases from group 1 and 7 cases of group 2 lost their follow-up which were excluded from the study. Total 86 patient completed the study, 43 in treatment group 1 and 43 in control group 2. Mean age of patient was 42.58±16.147 years in group 1 and 32.07±9.917 years in group 2. Majority of patient 56 (65%) were of age 20-40 years. Recurrence of stricture was seen in 9 (20.93%) cases in group 1 and 20 (46.51%) cases in group 2. Conclusions: The study concluded that clean intermittent self-catheterization is a simple and effective way of reducing the chances of recurrence after internal optical urethrotomy.